Attrition of TCR Vα7.2+ CD161++ MAIT Cells in HIV-Tuberculosis Co-Infection Is Associated with Elevated Levels of PD-1 Expression - Saeidi, Alireza; Tien Tien, Vicky L.; Al-Batran, Rami; Al-Darraji, Haider A.; Tan, Hong Y.; Yong, Yean K.; Ponnampalavanar, Sasheela; Barathan, Muttiah; Rukumani, Devi V.; Ansari, Abdul W.; Velu, Vijayakumar; Kamarulzaman, Adeeba; et al. (PloS one, 2015)
Mucosal-associated invariant T (MAIT) cells are evolutionarily conserved antimicrobial MR1-restricted CD8(+) T cells co-expressing the semi-invariant TCR Vα7.2, and are numerous in the blood and mucosal tissues of humans. MAIT cells appear to undergo exhaustion in chronic viral infections. However, their role in human immunodeficiency virus type 1 (HIV-1) mono-infection and HIV/tuberculosis (TB) co-infection have seldom been elaborately investigated. We conducted a cross-sectional study to investigate the frequencies and phenotypes of CD161(++)CD8(+) T cells among anti-retroviral therapy (ART)/anti-TB therapy (ATT) treatment-naïve HIV/TB co-infected, ART/TB treated HIV/TB co-infected, ART naïve HIV-infected, ART-treated HIV-infected patients, and HIV negative healthy controls (HCs) by flow cytometry. Our data revealed that the frequency of MAIT cells was severely depleted in HIV mono- and HIV/TB co-infections. Further, PD-1 expression on MAIT cells was significantly increased in HIV mono- and HIV-TB co-infected patients. The frequency of MAIT cells did not show any significant increase despite the initiation of ART and/or ATT. Majority of the MAIT cells in HCs showed a significant increase in CCR6 expression as compared to HIV/TB co-infections. No marked difference was seen with expressions of chemokine co-receptor CCR5 and CD103 among the study groups. Decrease of CCR6 expression appears to explain why HIV-infected patients display weakened mucosal immune responses.